A Competitive Assay Based on Dual-Mode Au@Pt-DNA Biosensors for On-Site Sensitive Determination of Carbendazim Fungicide in Agricultural Products - Chen, Ge; Zhai, Rongqi; Liu, Guangyang; Huang, Xiaodong; Zhang, Kaige; Xu, Xiaomin; Li, Lingyun; Zhang, Yanguo; Wang, Jing; Jin, Maojun; Xu, Donghui; Abd El-Aty, A. M. (Frontiers in Nutrition, 2022)
Introduction：Carbendazim (CBZ), a systemic, broad-spectrum benzimidazole fungicide, is widely used to control fungal diseases in agricultural products. Its residues might pose risks to human health and the environment. Objective：Therefore, it is warranted to establish a rapid and reliable method for its residual quantification. Herein, we proposed a competitive assay that combined aptamer (DNA) specific recognition and bimetallic nanozyme Au@Pt catalysis, which more stable, low cost and easy preparation than classical enzyme, to trace the carbendazim residue. Methods：The magnetic Fe3O4 was functionalized with complementary strand of DNA (C-DNA) to form Fe3O4 probes (Fe3O4-C-DNA). The carbendazim and the Fe3O4 probes competitively react with DNA modified nanozyme Au@Pt to form two Au@Pt-DNA biosensors (Au@Pt-DNA-CBZ biosensor and Au@Pt-dsDNA-Fe3O4 biosensor, respectively). The Au@Pt-DNA-CBZ biosensor was designed for qualitative analysis through naked-eye visualization strategy in the presence of carbendazim. Additionally, Au@Pt-dsDNA-Fe3O4 biosensor was developed to quantitatively analyze carbendazim using multifunctional microplate reader. Results：The LOD and recoveries of the developed assay were 0.038 ng/mg and 71.88%-110.11% with RSDs in between 3.15%-10.91%. The assay demonstrated excellent correlation with data acquired from LC-MS/MS analysis. Conclusion：In sum, the proposed competitive assay based on dual-mode Au@Pt-DNA biosensors might have a great potential for on-site sensitive detection of pesticides in agro-products.